Possible Approaches for the Treatment of Alzheimer’s Disease through Analysis of Patent Documents - Karinne Marieta Carvalho; Eduardo Winter; Adelaide Maria de Souza Antunes (New Ideas Concerning Science and Technology Vol. 5, 2021)
Alzheimer’s disease (AD) is the most common cause of dementia and is becoming ever more prevalent as a result of increased longevity and consequent population aging. It is a chronic and progressive neurodegenerative disease and until now incurable. The main neuropathological characteristics of Alzheimer’s disease are associated with dysfunction of the beta-amyloid protein (A?) and the microtubule-associated protein tau, which results in neuronal degeneration. The drugs act to improve symptoms but have no disease-modifying effects and are therefore considered one of the greatest challenges of science. This study shows that research into AD is on the rise around the world because the pharmaceutical industry and research institutions are seeking new types of drugs to treat and even cure Alzheimer’s patients. By analyzing patent documents, we map out the potential future treatments for this disease, indicating the leading countries and pharmaceutical industries that have invested most in a bid to accelerate progress towards discoveries about the disease and the development of new drugs.